Systematic literature review on the adaptation of marketing practices in providing information services to UiTM students for COVID 19 / Ain Farahanim Yusree ... [et al.] - Yusree, Ain Farahanim; Husaini, Haslinda; Md Aziz, Siti Haidah; Rambli, Yanty Rahayu (Faculty of Information Management, 2022)
Marketing is satisfying clients' needs with products and services. Marketing involves determining what people want and changing products to satisfy those demands profitably. Without a well-thought-out marketing strategy, supplying services and information commodities is insufficient. A 21st-century library is an institution or source that provides unfettered access to information and services that fulfil clientele's existing and projected information needs. Identifying the fundamental components of marketing information services and developing an effective marketing plan and technique for disseminating services and products., is vital to harnessing marketing experiences and accept its broad framework.